2015
DOI: 10.4085/1062-6050-50.12.01
|View full text |Cite
|
Sign up to set email alerts
|

Exertional Heat Stroke and Susceptibility to Malignant Hyperthermia in an Athlete: Evidence for a Link?

Abstract: Objective: To describe the possible association (pathophysiologic and clinical features) between exertional heat stroke (EHS) and malignant hyperthermia (MH).Background: Both EHS and MH are acute and lifethreatening disorders. It has repeatedly been shown that EHS can occur in well-trained patients with known MH-associated mutation in the RYR1 gene in the absence of any extreme environmental conditions or extreme physical activity, thereby supporting a possible link between EHS and MH. In this case, a highly t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…In summary, by taking advantage of local heating technology, we demonstrated that abnormal RyR1 heat sensing caused HICR in RyR1 mutant–expressing HEK293 cells and in skeletal muscles from MH mice. These findings suggest that an additional positive feedback loop between thermogenesis and heat-sensing via heat-hypersensitive RyR1 mutants irrepressibly elevates body temperature during MH and, presumably, during exertional heat stroke under extreme environmental conditions ( 63 65 ).…”
Section: Discussionmentioning
confidence: 89%
“…In summary, by taking advantage of local heating technology, we demonstrated that abnormal RyR1 heat sensing caused HICR in RyR1 mutant–expressing HEK293 cells and in skeletal muscles from MH mice. These findings suggest that an additional positive feedback loop between thermogenesis and heat-sensing via heat-hypersensitive RyR1 mutants irrepressibly elevates body temperature during MH and, presumably, during exertional heat stroke under extreme environmental conditions ( 63 65 ).…”
Section: Discussionmentioning
confidence: 89%
“…Health conditions: Hypohidrosis (Lim et al., 2016); malignant hyperthermia (Poussel et al., 2015); altered cytokine production (Chang, 1993); type II fibre predominance (Hsu, Lee, Chang, Shieh, & Tsao, 1997); burns (Seth & Juliana, 2011); sympathectomy (Sihoe, Liu, Lee, Lam, & Cheng, 2007); sickle cell trait (Singer et al., 2018)…”
Section: Resultsmentioning
confidence: 99%
“…Individual volition Armstrong et al (1990) Being overweight or obese Bedno et al (2010Bedno et al ( , 2014; Chung and Pin (1996); Donoghue and Bates (2000); Epstein et al (1999); Gardner et al (1996); Moore et al (2015); Rav-Acha et al ( 2004 (Epstein et al, 1999;Armed Forces Health Surveillance Center, 2009Nelson et al, 2018b); sex (Armed Forces Health Surveillance Center" 2009Nelson et al, 2018a); ethnicity (Carter et al, 2005) Health conditions: Hypohidrosis (Lim et al, 2016); malignant hyperthermia (Poussel et al, 2015); altered cytokine production (Chang, 1993); type II fibre predominance (Hsu, Lee, Chang, Shieh, & Tsao, 1997); burns (Seth & Juliana, 2011); sympathectomy (Sihoe, Liu, Lee, Lam, & Cheng, 2007); sickle cell trait (Singer et al, 2018) Environmental factors Accumulation of thermal load (previous day of exposure); (Garzon-Villalba et al, 2006;Wallace et al, 2006); high wet-bulb globe temperature (Day & Grimshaw, 2005;Garzon-Villalba et al, 2006; Organizational factors Branch of Armed forces and personnel rank (Bedno et al, 2014;Armed Forces Health Surveillance Center, 2009Nelson et al, 2018a); early stage of recruit training and aptitude on entry (possible link to inexperienced personnel; Nelson et al, 2018b); intense physical work (Armstrong et al, 1990;Day & Grimshaw, 2005;O'Donnell, 1975); time into exercise (suggestive of rate of temperature increase; Epstein et al, 1999); geographical region (Be...…”
Section: Lifestylementioning
confidence: 99%
“…18,21 The remaining RYR1 variants were rare variants of unknown significance (VUS) and several neutral polymorphisms (Table 2). [17][18][19][20][21][22][23][24][25][26][27][28][29] There were five CACNA1S variants, p.Arg498His, p.Ser516Leu, p.Ser606Asn, p.Arg683Cys, p.Thr852Met, identified in this cohort. These rare variants (minor allele frequency\1%) are of unknown significance and have not been reported in association with MH.…”
Section: Systematic Reviewmentioning
confidence: 99%